DOUBLE TRACK RAILWAY PLANNING ONE THE TRACK KM 309+260 – KM 302+600 SECTION DIVRE IV TANJUNG KARANG: PERENCANAAN JALAN REL DOUBLE TRACK PADA LINTASAN KM 309+260 – KM 302+600 DIVRE IV TANJUNG KARANG - febriyadi febriyadi; Arif Setyaji; Exaudi; Nur Anisa Mardhotila; Muhammad Riski Arif; Nurwanda Sari; Siti Maulidina; Hadyan Arifin Bustam (Universitas Negeri Surabaya, 2026)
Coal distribution at PT Bukit Asam uses railway transportation. This is considered quite efficient given the capability of trains to carry both passengers and goods in large quantities in a single trip, making it very efficient for mass transportation and logistics distribution over medium to long distances. However, in terms of advantages, trains on a single track face limitations in distance, load, and traffic capacity. Planning a Double Track route offers advantages in addressing issues related to load and traffic capacity. This study aims to find solutions regarding the traffic load on a track by adding a railway line (Double Track) without changing the existing track. The railway route planning is designed based on factors of comfort, safety, security, economy, and environment. The Vertical Alignment planning includes 2 curves with a planned radius of 7000 m and a gradient value of 6.6‰. The material requirements for the planned railway structure consist of R60 Rails (497 units), Double Elastic Fasteners (41,400 units), Concrete Sleepers (10,350 units), Ballast Volume (7,173 ), Ballast Volume (15,897 ), Cut Volume (567,743 ), and Fill Volume (205,269 )